Invertibility conditions for nonlinear autonomous differential operators in the space of functions bounded on the axis - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.988.5+517.988.63 For nonlinear autonomous differential operators defined in the space of functions bounded and continuous on the axis, necessary and sufficient conditions of being C^1-diffeomorphisms are obtained.